2016
DOI: 10.1016/j.neuropharm.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Linalool reverses neuropathological and behavioral impairments in old triple transgenic Alzheimer's mice

Abstract: Alzheimer’s disease (AD) is an age-related progressive neurodegenerative disorder. Several types of treatments have been tested to block or delay the onset of the disease, but none have been completely successful. Diet, lifestyle and natural products are currently the main scientific focuses. Here, we evaluate the effects of oral administration of the monoterpene linalool (25 mg / kg), every 48 hours for 3 months, on aged (21–24 months old) mice with a triple transgenic model of AD (3xTg-AD) mice. Linalool-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 47 publications
(59 reference statements)
2
83
0
Order By: Relevance
“…Moreover, Zheng et al reported that linalool exerts anti-inflammatory effects through the induction of Nrf2 nuclear translocation and the expression of HO-1. [154] An in vivo study performed on aged mice and transgenic model of AD (3xTg-AD) showed that a chronic treatment with linalool induced a significant reduction of A-deposition, and in the levels of the pro-inflammatory markers p38 MAPK, NOS2, COX2 and IL-1β [155,156]. All these data suggest that linalool is able to reverse the histopathological hallmarks of AD and to restore cognitive functions via an antiinflammatory effect.…”
Section: Nature-based Ligands As a Source To Design Multitarget Drugsmentioning
confidence: 98%
“…Moreover, Zheng et al reported that linalool exerts anti-inflammatory effects through the induction of Nrf2 nuclear translocation and the expression of HO-1. [154] An in vivo study performed on aged mice and transgenic model of AD (3xTg-AD) showed that a chronic treatment with linalool induced a significant reduction of A-deposition, and in the levels of the pro-inflammatory markers p38 MAPK, NOS2, COX2 and IL-1β [155,156]. All these data suggest that linalool is able to reverse the histopathological hallmarks of AD and to restore cognitive functions via an antiinflammatory effect.…”
Section: Nature-based Ligands As a Source To Design Multitarget Drugsmentioning
confidence: 98%
“…Six of the studies in the review examined the use of linalool compounds in the management of pro-inflammatory cytokines (Table 2). Deepa and Anuradha (Deepa and Venkatraman Anuradha, 2013); Quintans-Júnior et al , Wu et al (Wu et al, 2014), ; Sabogal-Guaqueta et al (Sabogal-Guáqueta et al, 2016) revealed that 10 to 40 mg/kg of linalool taken orally reduced the proinflammatory cytokines TNF-α, IL-1β, IL-6, which had been increased by different inflammatory inducers. Furthermore, 25 mg/kg (p.o.)…”
Section: Acyclic Monoterpenesmentioning
confidence: 99%
“…In addition, natural products are considered as a source of potential molecules in the field of neuroprotection (Lara-Guzman et al, 2012; Ho et al, 2013; Sumi et al, 2013; Dong et al, 2014). Therefore, in order to find pharmacological alternatives for a more agile translation to humans, a systemic administration during 3 months in a late stage of the AD mice model has been evaluated, using various natural products as flavonoids by intraperitoneal administration and monoterpenes by oral administration, which surpresively reduced the β-amyloidosis, tauopathy, cognitive disorder and anxiety present in old triple transgenic mice model of AD (Sabogal-Guáqueta et al, 2015, 2016), which could be useful in different kind of neurodegenerative environment and different advanced stages with proinflammatory markers and synaptic deterioration as VCID. Bioavailability analysis and scaling the production will increase the possibility to develop a clinical trial from South America.…”
Section: Preclinical Studies and Molecular Targetsmentioning
confidence: 99%